Critical Review of Direct-Drive Electrical Machine Systems for Electric and Hybrid Electric Vehicles - Cai, Shun; Kirtley, James L.; Lee, Christopher H. T. (IEEE transactions on energy conversion, 2022)
With ever-increasing concern of fossil fuel storage and environmental pollution, transportation electrification has recently attracted extensive attention. In conventional propulsion systems, the engine is connected to the wheel through a clutch, reduction gearbox, and mechanical differential. The mechanical transmission inevitably results in power loss, noise, vibration, and additional maintenance. With elimination of the gearbox and transmission component, the direct-drive technique exhibits significant advantages of higher systematic efficiency, more flexible wheel control, and better passenger comfort. This paper aims to provide an overview of automobile direct-drive techniques and recent electrical machine developments for direct-drive propulsion systems. Benefits and limitations of various direct-drive machines are summarized and compared with typical industrial products. Finally, the opportunities, challenges, and future development trends are discussed in related to the research "hot spots".